Krisis Iklim dan Konflik Agraria: Ancaman Ganda terhadap Hak Asasi Manusia di Indonesia - Maria Fatima Muti; Brigita Hilda Taek; Samuel Riwu Ratu; Fadil Mas'ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The climate crisis and agrarian conflicts in Indonesia are deeply interconnected as dual threats to the fulfillment of human rights. Climate change worsens socio-ecological conditions in rural areas through environmental degradation, crop failures, and intensified natural disasters, while agrarian conflicts driven by industrial expansion and weak land rights protection marginalize indigenous peoples, farmers, and other vulnerable groups. This literature-based study reveals that the climate crisis amplifies inequalities in access to natural resources and increases the risk of human rights violations, highlighting the need for ecologically just and human rights–based policies to achieve sustainable development in Indonesia.